Potential Economic Sector Analysis in the Gunung Anyar and Sukolilo Distric in Surabaya City-East Java Indonesia - Wiwin Priana (Future Science)
Regional development for the purpose and effort can be successful with the local government needs to function properly. Therefore, regional development is an effort to develop and strengthen local governments in order to strengthen regional autonomy that is real, dynamic, harmonious and responsible. Sukolilo District is urban (Trade) and Gunganyar sub-district is industrial and agricultural, Two sub districts are still the type of area that is not developed and not prosperous Both sub-districts are state universities (Sukolio distric there is ITS (Intitut Tecnologi of Sepuluh Nopember) and in Gununganyar distric UPN Veteran East Java). Method of this results is research approach about GRDP analysis, Location quotient analysis, multiple effect analysis, local tipology analysis. The result of this research is Sukolilo distric is urban (Trade) and Gunganyar sub-district is industrial and agricultural (pond). The two sub-district are still the undeveloped and non-prosperous areas both sub-districts are state university (Sukolio Sub-district there are ITS and Gununganyar UPNV East Java.